Pelatihan Pengisian Kartu Skor Poedji Rochjati pada Ibu Hamil dalam Deteksi Dini Risiko Tinggi Kehamilan - Wan Anita; Ayu Sri Pratwi; Rummy Islami Zalni; Elsa Hayatun Najmi; Julia Elna (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Maternal mortality in Indonesia is still high where maternal mortality can be prevented. Various complications that arise during pregnancy, childbirth and postpartum can be detected as early as possible so that delays in complications can be reduced. The Poedji Rochjati Score Card (KSPR) is an effort to detect early complications in mothers as well as evidence of recording and reporting by midwives in finding complications cases. The purpose of the service is to provide skills for pregnant women in detecting the condition of pregnant women as early as possible through filling out the Poedji Rochjati Score Card. The court activity was attended by 10 pregnant women who were held at the Muda Setia Poskesdes, Bandar Sei Kijang District, Pelalawan Regency. The results of the service show the ability of pregnant women to carry out early detection through filling out the KSPR as many as 3 pregnant women. that training for pregnant women in using the Poedji Rochjati Scorecard is very necessary, because with pregnant women knowing every development of pregnancy every month, pregnant women become more concerned about the possible risks of pregnancy that might arise and immediately have their pregnancies checked by health workers. It is hoped that health workers, especially midwives, will be able to provide ongoing counseling to increase the knowledge of pregnant women in early detection of pregnancy risks through KSPR so that mothers can recognize earlier the risks of pregnancy that are being experienced so that pregnant women immediately check their pregnancies.